DAMPAK KOMUNIKASI SIARAN LANGSUNG TERHADAP PENGALAMAN SPIRITUAL JAMAAH DALAM MENDENGARKAN KHUTBAH SHALAT JUMAT DI MASJID DAN ONLINE - Ahmad Salman Farid (Sekolah Ilmu Dakwah dan Komunikasi Islam (STIDKI) Ar Rahmah, 2024)
This study explores the impact of live broadcast communication on the spiritual experience of congregants in listening to Friday prayer sermons in mosques and online platforms. With technological advancements, the method of delivering religious sermons has expanded, transcending the physical confines of mosques to digital arenas. The research aims to investigate how communication, particularly live broadcast, influences congregants' spiritual experiences. Using a mixed-method approach, data was collected from mosque attendees and online participants. The findings indicate that while physical presence in the mosque fosters a sense of community and direct engagement with the sermon, online platforms offer convenience and accessibility but may sacrifice a profound spiritual atmosphere. Disparities in audiovisual quality, social interactions, and distractions between the two settings affect the depth of spiritual engagement. Understanding these dynamics is crucial for religious leaders, mosque administrators, and policymakers to optimize the dissemination of religious messages to diverse audiences. This research contributes to discussions on the relationship between technology, communication, and spirituality in contemporary religious practices.